Rhetoric in the translation of selected kinship terms in the holy Quran into French and English - Al-Shams, Noor Hamid Abdullah; Al-Jbori, Sarmad Mohammed Essa (Penerbit Universiti Kebangsaan Malaysia, 2025)
Translating the Qur’anic real meaning into other languages is considered to be a unique challenge as it is deeply rooted in Arabic culture and language. Thus, this operation often loses the rhetoric and poetic beauty of the Qur’anic text, hindering a deep understanding of its spiritual and moral significance. This study constitutes a part of a comparison study of certain kinship terms in Qur’anic Arabic' abawayn / wâlidayn, zawj / ba'al, and imra’a / zawj / ṣaẖiba and their equivalents in French and English versions. It is actually about providing some details on these Arabic terms and their equivalents by examining how they have been used in the Qur’anic context to indicate specific meaning. It is divided into two main parts. The first discusses the issue of the rhetoric in the translation. The second analysis differentiates between French and English translations of these Qur’anic terms. This research aims to highlight the importance and the role of rhetoric in translating these terms into other languages in order to convey their meaning in an exact or even a correct way. The study concludes that gaps and shortcomings in the process of converting the meaning of kinship terms contribute to the distortion of the original meaning in general and the text in particular. The data analysis underscores the significance of distinguishing between seemingly synonymous terms to prevent misinterpretations. Moreover, by overlooking the cultural and linguistic nuances of these terms, translators may inadvertently convey inaccurate or incomplete meanings.